Design and Evaluation of Three-Point Hitch Dynamometer - Singh, Charanjit; Panesar, B S (Journal of Agricultural Engineering, 2008)
A three-point hitch dynamometer was designed, fabricated, calibrated and tested for measuring draft, vertical force and the moment acting on four different types of implements. The dynamometer consisted of three subassemblies: implement subassembly for attachment to the implement, transducer subassembly for sensing different forces and tractor subassembly for attachment to the tractor. As a complete unit, the force dynamometer extended the implement by about 190 cm to the rear of the tractor hitch point. A total of 16 strain gauges were mounted on the transducer subassembly. Four strain gauges measured draft, another four-measured vertical force and the remaining eight-measured moment. Strain gauges for measuring moment were mounted at the tube surface at 45degree to the tube axis. Three 9-volt batteries and IC 7805 capacitor were used for supplying constant 5-volt excitation voltage to all the three bridges. The dynamometer was calibrated for three different bridges viz. draft-bridge, vertical-bridge and moment-bridge at different angles of pull. Data were recorded using a data logger. Calibration equations were determined for all the three bridges. Draft, vertical force, moment and pull for planker, no-till drill, ridger and cultivator were determined using the three-point hitch dynamometer. Operational parameters of the selected implement were varied as per the requirement of the implement used. Regression coefficient for draft-bridge, vertical-bridge and moment-bridge were 0.998, 0.995 and 0.996. The complete dynamometer is about 980 mm wide, 630 mm high and weighs 115 kg.